1987
DOI: 10.3382/ps.0661264
|View full text |Cite
|
Sign up to set email alerts
|

Body Volume and Density of Live Coturnix Quail and Associated Genetic Relationships

Abstract: A device was developed for the nondestructive measure of body volume by air displacement. Two experiments were performed on Coturnix quail to determine the feasibility of using body density and volume of the live bird as criteria of selection for changing whole body lipid content. In Experiment 1,423 birds were used from three selected lines differing in adult weight. Three measurements of volume were taken on each bird. Repeatability of volume was consistently high for all line-sex subclasses, averaging .75. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
4
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 18 publications
2
23
4
2
Order By: Relevance
“…These high estimates agree with data in the literature on Japanese Quail. The heritability of body weight was reported to be 0-82 (Garwood & Diehl, 1987) and 0-84 for the metatarsus (Isogai, 1971). Data also agree with high responses to selection for body weight in Japanese Quail (Marks, 1988).…”
Section: (Ii) Heritabilities Of Growth Curve Parameters and Final Sizementioning
confidence: 97%
“…These high estimates agree with data in the literature on Japanese Quail. The heritability of body weight was reported to be 0-82 (Garwood & Diehl, 1987) and 0-84 for the metatarsus (Isogai, 1971). Data also agree with high responses to selection for body weight in Japanese Quail (Marks, 1988).…”
Section: (Ii) Heritabilities Of Growth Curve Parameters and Final Sizementioning
confidence: 97%
“…They have less feed requirement and an adult quail requires only 20-25 g feed per day compared to chicken (120-130g) per day (Ani et al, 2009). Other unique characteristics and advantages of quails over other species of poultry include early attainment of sexual maturity, being able to come to lay as early as 5-6 weeks of age, having short generation interval making it possible to have many generations in a year (Robbins, 1981;Annon, 1991), attaining market weight of 150-180 g between 5-6 weeks of age and a high rate of egg production between 180-250 (Garwood and Diehl, 1987) and 200-300 eggs in their first year of lay (NRC, 1991). Reports by Haruna et al (1997) and Olubamiwa et al (1999) showed that quail meat and eggs are renowned for their high quality protein, high biological value and low caloric content, making it a choice product for hypertension prone individuals.…”
Section: Haematological and Serum Biochemistry Proceduresmentioning
confidence: 99%
“…The meat and egg are delicious, noted for high dietary and even medicinal values (2). The meat is lean and both the egg and meat are low in cholesterol (3). Quails could be a good and economical source of animal protein because of their fast growth potential, early maturity, high rate of egg production, short generation interval and small body size that allows large number of birds to be kept in a small space.…”
Section: Introductionmentioning
confidence: 99%